Lamella-rod pattern transition and confinement effects during eutectic growth. (1st January 2023) - Şerefoğlu, Melis; Bottin-Rousseau, Sabine; Akamatsu, Silvère
Graphical abstract: Abstract: We present an in situ experimental study of the lamellar-to-rod transition during directional solidification of a model eutectic transparent alloy –the succinonitrile-(d)camphor (SCN-DC) system. Coupled-growth patterns, and their morphological transformations upon changes of the pulling velocity V ( 3.5 − 70.0 nms − 1 ) were observed in real time in a series of flat-wall samples with different thicknesses δ from 15 (thin samples) to 350 µm (thick samples). At relatively large velocity, rod-like patterns formed systematically. In contrast, stable lamellae were observed at sufficiently low velocity, regardless of the sample thickness in the investigated range. In confined-geometry samples ( δ = 30 − 140  µm), lamellar patterns were stable over a large range of the interphase spacing λ at low V . The lamella in contact with the sample walls were stabilized against a propagative breakup, and the formation of rods was mediated by secondary instabilities such as a zigzag mode and a spatial-oscillation mode. In the bistable range, a hysteresis upon increasing or decreasing V was observed, as well as complex phenomena involving oscillatory, mixed and hybrid patterns. The (reverse) transition from rods to lamellae involved a rod elongation instability. A discussion on the elementary mechanisms that determine the lamellar-rod transition, and their dependence on λ and V is initiated.